(untitled) (International Journal of Humanities and Information Technology, 2022)
Now-a-days more of the industries are moving towards the metal matrix because of its superiority behaviour such as in aeronautical, navigation space research & medical. It also plays a vital role in automobile, sports equipment and electronics due to their favorable properties like light weight, high strength and low coefficient of thermal expansion. The aluminium 7010 is mostly used in aerospace industries. The Al7010 has the high strength and moderate hardness but its properties can be improves by mixing some refractory materials such SiC. Different mechanical tests were conducted viz. Hardness test, Impact test & water corrosion test presented by varying the weight fractions of SiC. In this work a composite will develop by adding silicon carbide in Aluminium -7010 metal in ratio 2%, 5% and 7% by weight. The composite is prepared by melt stir casting technique in appropriate size (15*50*100) mm